Retrofitting SBR systems to nutrient removal in sensitive tourist areas - Tasli, R.; Artan, N.; Orhon, D. (IWA Publishing, 2001)
Retrofitting of existing SBR systems for nutrient removal is evaluated and defined for small communities in sensitive coastal areas, with seasonal fluctuations in wastewater quantity and quality. The proposed approach is developed by means of basic process stoichiometry and verified using ASM2d. The efficiency of retrofitting is found to rely on the delicate balance between the overall sludge age, the initial settled sludge volume in the reactor, and the ratio of the initial volume to the feed volume in each cycle, a parameter corresponding to the recycle ratio in continuous systems.
Keywords: Quality Control; Sewage; Nitrogen; Phosphorus; Equipment Design; Waste Disposal, Fluid; Water Purification; Bioreactors; Recreation; Seasons